How do appraisal as threat or challenge, efficacy, and environmental quality affect wellbeing in the COVID-19 pandemic? - Wallis, Hannah; Holzen, Veronique; Sieverding, Theresa; Matthies, Ellen; Schmidt, Karolin (Frontiers in Psychiatry, 2023)
Background: In crises, it is of great relevance to identify mechanisms that help people to maintain a certain level of well-being. This paper investigates whether appraising the COVID-19 pandemic as a threat vs. as a challenge has different effects on subjective well-being during the pandemic. Furthermore, we study the role of the perceived local environmental quality for individuals’ subjective well-being. Methods: Via online survey study with two times of measurement (N = 758), we investigated a) the prediction of participants’ well-being in June 2020 and June 2021 through five variables and b) how these five variables moderated within-participant differences in subjective well-being over time. Results: Results showed that a stronger perception of the pandemic as a threat (feeling worried) and a lower education in June 2020 predicted a lower subjective well-being in 2020 and 2021. A stronger challenge appraisal (feeling confident), higher efficacy expectations, and positive perceptions of the local environmental quality in June 2020 predicted a higher well-being in 2020 and 2021. There was no substantial change in participants’ aggregated well-being over time. However, those who perceived the pandemic more as a threat in June 2020 struggled more with negative changes in their well-being, whereas those who perceived the pandemic more as a challenge reported a higher well-being. Conclusion: It seems key to support people in activating positive feelings to successfully cope with crises.